Efektivitas Model Problem Based Learning dan Make A Match dalam Pembelajaran Tematik Kelas V SD Negeri 2 Gondang - Permatasari, Dian Ayu (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2020)
AbstractAbstract: Problem-Based Learning Model and Matching in Thematic Learning at fifth grade students of 3 SD Negeri Bugangan 01 and SD Negeri 2 Gondang viewed from the appearance of critical thinking. The subjects in this study were fifth grade students at SD Negeri Bugangan 1Â  Elementary School as an experimental class and SD Negeri 2 Gondang Elementary School as a control class. This type of research is a quasi-experimental research type Test-Posttest Control Group Design. The Samples are 72 students. The results showed that the use of Problem Based Learning model can enhance learning about critical problems in Thematic subjects in fifth grade stdents at of 3 SD Negeri Bugangan 01 and SD Negeri 2 Gondang. It can be prove from what is supported by studentâ€™s critical thinking from the experimental class 74.21 (quite critical) and the control class 60.82 (uncritical). From the Ancova test on the calculation of Indonesian Language 1,570 level of significance or probability is 0.214. Therefore the probability is 0.214. Because of the probability 0.214 0.05, Ho is accepted, and Ha is rejected. While on the charge of Natural Sciences F count 0.334 level of significance or probability 0.565, then Ho is accepted and Ha is rejected. Related to the effective Problem Based Learning model in the Make A Match model in terms of Thematic critical thinking in fifth grade students of of 3 SD Negeri Bugangan 01 and SD Negeri 2 Gondang..Keywords: Effectiveness,Problem Based Learning and Make a Match Learning Model, identifying the type of work